2013
DOI: 10.1021/ef400925e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Adsorption of Organic Compounds Dissolved in Synthetic Produced Water at Air Bubbles: The Influence of the Ionic Composition of Aqueous Solutions

Abstract: A detailed analysis of the dynamic adsorption of crude oil components dissolved in produced water onto air bubble surfaces is presented. Synthetic produced water was prepared using three crude oils and aqueous solutions with varying ionic composition. The total organic carbon content, molecular mass, and dynamic surface tension was determined for the samples. A modified version of the Ward−Tordai model was used to evaluate the experimental data. This allowed for determination of the characteristic diffusion co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
5
21
0
Order By: Relevance
“…[ 70 ] Regarding surface activity, several studies show that although small amounts of organic compounds are present in water, these soluble amphiphilic components have a considerable effect on surface/interface property. [ 43,44,54 ] Comparing the results of this work with previous research, it can be concluded that some organic compounds of crude oil are soluble in water and their amount varies according to the type of oil and polar compounds.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…[ 70 ] Regarding surface activity, several studies show that although small amounts of organic compounds are present in water, these soluble amphiphilic components have a considerable effect on surface/interface property. [ 43,44,54 ] Comparing the results of this work with previous research, it can be concluded that some organic compounds of crude oil are soluble in water and their amount varies according to the type of oil and polar compounds.…”
Section: Resultssupporting
confidence: 52%
“…These functionalities alongside organic tail could act as surface‐active components and affect the IFT/ST and wettability. [ 43,44,54 ] The analysis of well‐produced water shows that the most soluble components of crude oil are carboxylic acids with a low molecular weight. [ 72 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has previously demonstrated the effect of the dissolved components on the air-water interface 20,[57][58] and the flotation performance 59 . In this section we discuss their influence on the coalescence between crude oil droplets.…”
Section: Dissolved Components -Model Systemsmentioning
confidence: 99%
“…In a series of recent papers we have investigated the adsorption of the water-soluble crude oil components onto bubble surfaces. It was demonstrated that the adsorption was rapid and that both the acidic and basic components in the crude oils had affinity for the bubble surfaces. However, no correlations to the total acid and base numbers of the crude oils were found.…”
Section: Introductionmentioning
confidence: 99%